From Ismant Al-Kharab to Nag Hammadi: Some Observations about Ideological Diversity in Fourth Century Groups of Coptic Manuscripts - Camplani, Alberto (Studi e materiali di storia delle religioni, 2020)
The Kellis (Ismant al-Kharab) find of documentary and literary papyri shows the real cultural life of a Manichaean community. It is the first time that a discovery puts in strict connection literary and liturgical manuscripts with the context in which they were read or produced, that is, a Manichaean community. The texts are interesting also from the linguistic point of view, as they attest to a developed Greek / Egyptian diglossia, as well as the familiarity with Manichaean Syriac. In the paper this evidence is compared to that provided by other discoveries of Coptic manuscripts such as those of Medinet Madi, Nag Hammadi and Dishna, and is used to give new arguments in the debate about the monastic origins of the Nag Hammadi codices.